Managing urbanisation : growth strategies for South African cities with special reference to the Cape Town metropolitan area - Van Gend, R. B.(Rowan Benjamin) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. in Town and Regional Planning) -- University of Stellenbosch, 1991.